(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
The article compares three linguistic zoomorphic pictures of the world – Chinese, Japanese and Indian. It deals with zoometaphors, which are inconsistent with the principle of ascending from the abstract to the concrete, but realize the prototypical effect, presenting some characteristics by concrete notions. These metaphors are of great importance in the process of human thinking as they perform the evaluative-expressive and aesthetic functions of language. They express some social types and standards of human behavior, evaluate both extrinsic characteristics and intrinsic features of the person. The more distant the cultural areas are, the more differences are present in linguistic zoomorphic pictures of the world.